2001
DOI: 10.1046/j.1365-2249.2001.01539.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral administration of unmodified colonic but not small intestinal antigens protects rats from hapten-induced colitis

Abstract: SUMMARYColonic administration of a hapten, 2,4,6-trinitrobenzene sulphonic acid (TNBS) has been shown to induce colitis in rats. We are using this model to investigate the role of colonic antigens in the immunopathology. In this study, we show that colitis can be suppressed by oral administration of haptenized colonic antigens prior to the TNBS enema. Moreover, our data suggest that haptenization of the colonic antigens is not essential because oral feeding of non haptenized colonic antigens too protects rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…TNBS-induced colitis in rats can also be prevented by feeding either human colon epithelial cells or rat colonic epithelial extracts, but not human fibroblasts nor rat small intestine extracts, showing that tolerance is organ specific. Protected animals had low IFN-g and high TGF-b levels and tolerance could be transferred by mesenteric lymph nodes cells (Dasgupta et al 2001). In addition, colitis can be suppressed via bystander suppression by transfer of OVA transgenic CD4þ -CD45 high T cells (from DO.11.10 mice) into SCID mice (Zhou et al 2004).…”
Section: Colitismentioning
confidence: 99%
“…TNBS-induced colitis in rats can also be prevented by feeding either human colon epithelial cells or rat colonic epithelial extracts, but not human fibroblasts nor rat small intestine extracts, showing that tolerance is organ specific. Protected animals had low IFN-g and high TGF-b levels and tolerance could be transferred by mesenteric lymph nodes cells (Dasgupta et al 2001). In addition, colitis can be suppressed via bystander suppression by transfer of OVA transgenic CD4þ -CD45 high T cells (from DO.11.10 mice) into SCID mice (Zhou et al 2004).…”
Section: Colitismentioning
confidence: 99%
“…Lamina propria CD4 + T cells exhibit a Th1 pattern of cytokine secretion, with an increase in IFN‐γ and IL‐2 and a decrease in IL‐4 secretion. Induction of oral immune regulation toward colitis‐extracted proteins (CEP) alleviated experimental colitis, manifested by a decrease in diarrhea, percentage of affected colonic area, degree of colonic ulceration, intestinal and peritoneal adhesions, and wall thickness 12–14. Histologic evaluation of bowel tissue showed marked reduction in inflammatory response and mucosal ulceration (Fig.…”
Section: Oral Immune Regulation In Experimental Colitismentioning
confidence: 99%
“…When suppressor T cells activated by antigen‐presenting cell (APC) presentation of these proteins encounter similar epitopes in the colon, they secrete anti‐inflammatory cytokines 17. A recent study demonstrates that cellular proteins from human colon epithelial cells, but not from human fibroblasts, can induce oral tolerance in experimental colitis 13,14. It was recently suggested that haptenization of the colonic antigens is nonessential because oral feeding of nonhaptenized colonic antigens also protects rats from TNBS‐induced colitis 14…”
Section: Oral Immune Regulation In Experimental Colitismentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that oral colitis-extracted proteins (CEP) or normal colon-extracted proteins with five low doses can prevent experimental colitis induced by TNBS in rodent animals. Tolerance induction was mediated by immunosuppressive cytokines such as TGF-β and so on [24][25][26]. Dextran sodium sulfate (DSS)-induced colitis is also a widely used animal model for researching the pathogenesis and treatment of human IBD [27][28][29].…”
Section: Introductionmentioning
confidence: 99%